Geomorfologi Daerah Tambang Emas Rakyat Juriya dan Sekitarnya, Kecamatan Bilato, Kabupaten Gorontalo - Rauf, Jayanti; Arifin, Yayu Indriati; Akase, Noviar (Universitas Negeri Gorontalo, 2024)
This study examines the geomorphological characteristics of the Juriya people's gold mining area, Gorontalo Regency, which includes topographic variations, slopes, river flow patterns, river stadia, and geomorphological units. The research area is divided into four main morphometry types: Lowland, Inland Lowland, Low Hill, and Hill. Slope analysis identifies zones ranging from flat to very steep, indicating different levels of slope stability and areas with a high risk of erosion. The results of the river flow pattern analysis showed the dominance of parallel and dendritic patterns, with a